Modeling domestic pancake cooking incorporating the rheological properties of the batter. Application to seven batter recipes. (February 2021) - Lorente-Bailo, Silvia; Etayo, Iñigo; Salvador, María L.; Ferrer-Mairal, Ana; Martínez, Miguel A.; Calvo, Begoña; Grasa, Jorge
Abstract: A 2D axisymmetric model for coupled transient heat and mass transfer was developed to simulate pancake cooking on a domestic induction hob. Unlike previous models, the current model considers a variable thermal contact conductance resulting from the crust formation at the bottom of the batter. It aims to take into account the heat transfer phenomena between the pan surface and the batter influenced by the physicochemical changes that the batter undergoes during the cooking process. To quantify the variation of the heat flow that this change in the structure of the batter involves, a normalized relationship between batter viscosity and the temperature was introduced in the model. The performance of seven cereal and legume flour-based batters was evaluated in an experimental setup. The proposed model is capable of adequately predicting the weight loss and the average surface temperature of the batter using parameters related with the rheological properties of the batter and its composition. Highlights: Updating of existing models to simulate domestic cooking of pancakes. Deep insight into changes in the interface between the hot surface and the pancake. Evaporation rate and heat conductance are related to rheological properties. Apparent viscosity reflects inverse dependence with the weight loss during cooking. Optimized model parameters are useful to understand the cooking performance of batters.